Assessment of Neoadjuvant Chemotherapy Response In Carcinoma Breast Patient By High Frequeny Ultrasound. - Dighe, Sajika Pramod; Shinde, R K (International Journal of Psychosocial Rehabilitation, 2020)
Neoadjuvant chemotherapy for carcinoma breast was discovered historically for inoperable tumor. This Study is about neoadjuvant chemotherapy response between caf and taxane in carcinoma breast patients by high frequency ultrasound in female patients. With the discovery of new neoadjuvant type of chemotherapy for locallyadvanced or dispersed carcinoma breast patients , the cure rate and metastasis rates have been decreased. While caf is the 1st line neoadjuvant chemotherapy in cases of locally advanced carcinoma breast, the new evolving 2nd line paclitaxel neoadjuvant type chemotherapy is working wonders in the same group of patient creating a new path for study of these new chemotherapy drugs. High high frequency Ultrasound is used to study the response of both of these neoadjuvant type chemotherapy and the best of them is further decided and hence then proved. In patients with axilla positive the new use of neoadjuvant taxane based chemotherapy shows a path breaking result than Adriamycin based neoadjuvant chemotherapy thus increasing the overall survival rate and disease free rate in patients of metastatic and locoregional spread of carcinoma breast patients.